Beyond traditional developmental models: a fresh perspective on entrepreneurial new venture creation. (10th April 2015) - Becker, Alexander; Knyphausen–Aufseß, Dodo zu; Brem, Alexander
Opportunity discovery and creation are key areas of research in entrepreneurship literature. Based on the ongoing discussion, this paper proposes an integrative view of a dynamic multi–stage new venture emergence. In particular, the findings of our research show how to match these approaches with the life cycle stages of an emerging venture. This paper contributes to existing entrepreneurship research by acknowledging the value of parallel sequential process combinations, by including customer demand as part of a market participant's selection criteria, and by recognising failure as valuable outcome. The implication for entrepreneurs is that, beyond discovering a potential venture idea, substantial development efforts are required to form a sustainable business model. For entrepreneurship research, our model is a first step towards an integrative discussion of new venture emergence aimed at fostering further research and the advancement of new theoretical insights.